The Impact of Risk Management, Liquidity, and Leverage on the Financial Performance of Manufacturing Companies Listed on the Indonesia Stock Exchange - Ahmad Nur Budi Utama; Fera Lufhidarani Pranita (West Science Accounting and Finance, 2024)
This study examines the impact of risk management, liquidity, and leverage on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX). Utilizing a quantitative approach, data from 160 companies were collected using a structured survey and secondary financial data. The study employs Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze the relationships between these factors. The results reveal that all three factors—risk management, liquidity, and leverage—have a significant positive effect on financial performance. Specifically, companies with stronger risk management practices, higher liquidity, and optimal leverage levels tend to demonstrate better financial outcomes. These findings provide valuable insights for corporate managers, investors, and policymakers, highlighting the importance of effective financial management in fostering sustainable business growth in the manufacturing sector. This research contributes to the understanding of financial performance drivers in emerging markets and offers practical recommendations for improving business performance.